(untitled) (Research, Society and Development, 2022)
Introduction: Syphilis is an infectious disease caused by the virulence of the microorganism Treponema pallidum, which can be classified as acquired, gestational and congenital syphilis. Method: Descriptive, comparative and bibliographic research. Results: The highest rate of infection cases was found in women with an incomplete 5th to 8th grade level of education, with a total of 30 cases, in 2019, this same level of education also recorded, in 2020, 265 cases. In the age group, it is observed that in 2019 and 2020, the highest rates of infection occurred in those aged 20 to 39 years, respectively, with 61 and 627 cases of gestational syphilis. In metropolitan regions, the highest rates in the capital of RN stand out, in 2019 and 2020, with 58 and 582 cases of gestational syphilis, respectively. Non-treponemal tests recorded in 2019, 3.72% (n=78), while in 2020, 77.5% (n=646) of reactive cases were through non-treponemal tests. Treponemal tests, in 2019, were 27.2% (n=59), in 2020 they reached 71.4% (n=595). As for the level of infection: the highest number of cases occurred, in 2019 and 2020, at the primary level, the respective values: 37 and 313. Conclusion: The doctrine finds the need to maintain, exhaustively, the focus on the creation of preventive measures aimed at eradicating the contagion of the microorganism, as well as the creation of public policies that facilitate access to diagnostic tests for Treponema and access to specific therapy early.